Using genetic programming to model process of robot laser hardening - Babič, Matej; Kovač, Pavel; Savkovic, Borislav (Journal of Production Engineering, 2019)
This article describes the fractal geometry of robot laser hardening microstructure at different parameter. We show the experimental results and analysis of fractal patterns that occur in robot laser hardening at different parameter. In the end we present fractal geometry in point robot laser hardening pattern. Robotic laser hardening is used in the aerospace, automotive and military industries. Fractals can be defined in many ways, the simplest definition being that they do not change shape with scale, and thus they exhibit self-similar properties. Their fundamental property is fractal dimension D, which yields important insights into the physical properties of geological objects. Fractals are a beautiful of mathematics and art. Perhaps this is the reason why most people recognize fractals only as pretty pictures useful as backgrounds on the computer screen or original postcard patterns. The fractal patterns look complex in robot laser hardened patterns to. Fractal structures can be find in robot laser hardened patterns to if it was observed it with electron microscope. Robot laser surface hardening heat treatment is complementary to the conventional flame or inductive hardening. In this work we have used scanning electronic microscope (SEM), search and analyze the fractal structure of the robot laser-hardened material. It was use method of intelligent system, namely genetic programming to model hardness in depth of robot laser hardening.